2014
DOI: 10.5539/jgg.v6n4p164
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Macroalgal Blooms as Indicators of Nutrient Loading from Aquifer-Injected Sewage Effluent in Environmentally Sensitive Near-Shore Waters Associated with the South Florida Keys

Abstract: Domestic wastewater is injected into Florida's permeable aquifer system via Class I and Class V wells theoretically to avoid nutrient loading and other contamination that occurs when domestic wastewater is discharged directly to surface waters, resulting in nutrient loading and harmful algal blooms (HABs). The majority of Class I aquifer-injection wells are used to inject secondary-treated effluent from domestic wastewater treatment plants. Class V aquifer-injection wells also include injection of domestic was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…These are not the only CUP wells that may occur or have occurred during that mining operation. The acquisition and methods for the FDOT (1973) and Vernon (1951) mapped lineaments indicative of fractures in Florida were described in Bacchus et al (2014), Bernardes et al (2014), and Lines et al (2012). The Digital Elevation Models (DEMs) used to illustrate the lateral extent and relative depths of flooding associated with Hurricane Irma in the lower SFR vicinity of O'Leno State Park and Buzzards Roost Prairie, were obtained from the SRWMD.…”
Section: Shapefiles and Other Data Obtained From Agenciesmentioning
confidence: 99%
“…These are not the only CUP wells that may occur or have occurred during that mining operation. The acquisition and methods for the FDOT (1973) and Vernon (1951) mapped lineaments indicative of fractures in Florida were described in Bacchus et al (2014), Bernardes et al (2014), and Lines et al (2012). The Digital Elevation Models (DEMs) used to illustrate the lateral extent and relative depths of flooding associated with Hurricane Irma in the lower SFR vicinity of O'Leno State Park and Buzzards Roost Prairie, were obtained from the SRWMD.…”
Section: Shapefiles and Other Data Obtained From Agenciesmentioning
confidence: 99%
“…Locations [33] lineaments in Florida were described in Bacchus et al [29] and Lines et al [24]. This is the most extensive fracture network mapped in …”
Section: Shapefiles and Other Data Obtained From Agenciesmentioning
confidence: 99%
“…Bacchus et al [29] presented evidence of the distance from the source that adverse impacts to habitat can occur as the result of preferential flow through fractures. The results of that study suggested that preferential flow occurred through the areas of the panther habitat studies described above.…”
Section: Introductionmentioning
confidence: 99%
“…The reported "recovery" in the US Geological Survey (USGS) review of ASR wells and well data in Florida (Reese, 2002, Table 5) was based on the chloride concentration established under the SDWA for potable water (250 mg/L), rather than the much lower chloride concentration of the water injected into those ASR wells. Actual "recovery" was determined by adjusting the results of cycle testing conducted in ASR test wells constructed in south Florida to compensate for differences between chloride concentration of water injected into ASR wells and water withdrawn from those wells (i.e., reported chloride concentration/(recovered/injected concentration)), as summarized by Bacchus et al (2014;2015a;2015b). Actual "recovery," based solely on chloride content of the withdrawn water adjusted to match the chloride content of the injected water ranged from 0% to 16.8% for "storage" periods of 15 and 8 days, respectively for those ASR wells (Table 3 of Bacchus et al, 2015a).…”
Section: The Theory Of Asrmentioning
confidence: 99%
“…Evidence that these injected wastes rapidly flow through preferential pathways in the karst aquifer system, then discharge into nearshore coastal water, was summarized by Bacchus et al (2014). Bacchus et al (2015a) illustrated the proximity and frequencies of permitted ASR wells, other injection and withdrawal wells, to reported modern sinkholes, mapped fractures and fracture intersections in Florida.…”
Section: Strategic Location Of Asr and Other Injection And Withdrawalmentioning
confidence: 99%